O Chaos das 5 - Schiavoni, Flávio Luiz; Siqueira, Adilson; Constante, Rogério Tavares; Silva Junior, Igino de Oliveira; Morandi, Thiago de Andrade; Carvalho, Fábio dos Passos; Araújo, João Teixeira; Gomes, André Lucas Nascimento; Resende, Frederico Ribeiro; Santos, Luísa Lugon-Moulin Brazil; de Paulo, Avner Maximiliano; de Souza, Carlos Eduardo Oliveira; et al. (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
“O Chaos das 5” is an audiovisual digital performance. The guideline of the performance is inspired by Alice, from Lewis Carroll book - Alice in the Wonderland, as a metaphor to take the audience to a synthetic and disruptive wonder world. The concept of the performance is to conceive the possibility to the audience to interact through digital interfaces creating an immersive and participatory experience by combining three important layers of information (music, projections and gestures) through their cellphones. Once that the audience members take part of the show on an immersive aspect, there is no stage or another mark to limit the space of the performers and the audience.